Organ Transplantation from Deceased Donor: myths and facts in Pakistan and world over. - Naqvi, Rubina (Pakistan Journal of Kidney Diseases, 2023)
Organ transplantation is remarkable scientific achievement in treatment of patients with end stage organ failure. Renal transplant was first solid organ transplant performed in early 50s. Initially only transplant from living donors were performed but later keeping in view of number of patients suffering from end stage organ failure and shortage of living donors, practice of retrieving organs from dead has been adopted. Such donors previously called ‘cadaver’ and now labelled as ‘deceased’ donors can be non-heart beating donors or donors with circulatory failure or could be brain dead donors. This article highlights types of organs which can be harvested from deceased donors. The ethical dimensions (which covers social, cultural, legal, religious and ethical issues) of deceased organ donation and their impact. Verdicts from religious point of view of different world religions is referred at end of article as consideration of religion cannot be denied in field of transplantation. This article also highlights definition and diagnosis of brain death, conditions necessary to fulfil retrieving organs from brain death and the ethical dimensions (which covers social, cultural, legal, religious and ethical issues) of organ donation from brain dead.